New aspect of studying the mechanisms of development of the lungs ventilation capacity disorders in children with bronchial asthma - Shumna, T. Ye.; Fedosieieva, O. S.; Kamyshnyi, O. M. (Journal of Education, Health and Sport, 2020)
Purpose. Study of the pathogenetic role of the polymorphism of the ACTN3 gene (actinin, alpha 3) rs1815739 in the development of lungs ventilation capacity disorders in children with bronchial asthma. Materials and methods. To study the polymorphism of ACTN3 gene (actinin, alpha 3) rs1815739, the molecular and genetic study of 90 children aged from 6 to 18 years with bronchial asthma, who were passing in-patient treatment at the Allergy Department of the Municipal Non-Profit Enterprise "Children’s Hospital no.5" of Zaporizhia City Council, and 25 healthy children (control group) was conducted. The external respiration function was studied using a computer spirograph "PULMOREM" TU U 33.1-02066769-005-2002 (Kharkiv). The study of the polymorphism of the ACTN3 gene (actinin, alpha 3) rs1815739 was performed in the Division of Molecular Genetic Researches of the Training Medical Laboratory Center at the Department of Microbiology of Zaporizhia State Medical University in Zaporizhia on the CFX96TM Real-Time PCR Detection Systems amplifier (Bio-Rad laboratories Inc., USA) with extraction of DNA from venous blood by means of polymerase-chain reaction. The results of the study were processed using statistical analysis of the license software package Statistica for Windows 6.1.RU, serial number AXXR712D833214SAN5. Results. The study of the distribution of allelic genes and genotypes of ACTN3 (actinin, alpha 3) polymorphism for rs1815739 showed that among children with bronchial asthma, the homozygous C/C genotype was recorded in 37.7% of cases, heterozygous C/T genotype in 40% of cases, homozygous T/T genotype in 22.3% of cases, while in healthy children, the frequencies of the homozygous C/C (68%) and T/T (4%) genotypes were significantly more frequent. The indicators of external respiration function (forced vital capacity (FVC), forced expiratory volume at the 1-second (FEV1)) in patients with a homozygous C/C genotype were significantly lower than in patients with homozygous T/T genotype and were 2.69 (1.9; 3.49) vs. 3.11 (2.47; 4, 14) and 2.06 (1.6; 2.76) vs. 2.82 (2.02; 3.51). The patency of large and small bronchi, characterized by spirographic MEF25 and MEF75 indicators, was significantly better in children with bronchial asthma with homozygous T/T genotype than in children with C/T and C/C genotypes (5.46 (4.87; 6, 31) and 2.36 (1.89; 3.32) against 4.54 (3.69; 5.43) and 4. 17 (3.24; 5.44), and 1.88 (1.10; 2.56) and 1.69 (1.16; 2.02), respectively. In children with bronchial asthma and the C/C and C/T genotypes of ACTN3 gene (actinin, alpha 3) rs1815739 with probable sufficient synthesis of alpha-actinin-3 protein in muscles, a stronger contraction of the respiratory muscles on inhalation is possible, and in patients with the T/T genotype, which encodes insufficient synthesis of alpha-actinin-3 protein in the muscles, the muscle contraction is probably less pronounced in asthma attacks, which can lead to less pronounced disorders of lungs ventilation capacity. Conclusions. The study of ACTN3 (actinin, alpha 3) rs1815739 gene polymorphism showed that the C / C and C / T genotypes were associated with impaired lung ventilation in children with bronchial asthma.